2021
DOI: 10.3390/ijms22179533
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Properties of Sweet Potato Starch for Industrial Applications by Biotechnological Techniques including Genome Editing

Abstract: Sweet potato (Ipomoea batatas) is one of the largest food crops in the world. Due to its abundance of starch, sweet potato is a valuable ingredient in food derivatives, dietary supplements, and industrial raw materials. In addition, due to its ability to adapt to a wide range of harsh climate and soil conditions, sweet potato is a crop that copes well with the environmental stresses caused by climate change. However, due to the complexity of the sweet potato genome and the long breeding cycle, our ability to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 141 publications
(194 reference statements)
0
6
0
Order By: Relevance
“…CRISPR-Cas9 gene editing technology, which allows precisely targeted genome modifications, has been used successfully to edit two starch biosynthetic pathway genes ( GBSSI and SBEII ) in sweetpotato. In GBSSI knockout plants, the amylose content was reduced, and in SBEII knockout plants, the amylose content was increased ( Wang et al., 2019 ; Lyu et al., 2021 ).…”
Section: Progress In Sweetpotato Breedingmentioning
confidence: 99%
“…CRISPR-Cas9 gene editing technology, which allows precisely targeted genome modifications, has been used successfully to edit two starch biosynthetic pathway genes ( GBSSI and SBEII ) in sweetpotato. In GBSSI knockout plants, the amylose content was reduced, and in SBEII knockout plants, the amylose content was increased ( Wang et al., 2019 ; Lyu et al., 2021 ).…”
Section: Progress In Sweetpotato Breedingmentioning
confidence: 99%
“…In a closed-loop system for starch, genetic modification, seed creation, growth, and delivery to the processing mill are all perfectly controlled. Genome editing [ 102 ] and genetic and environmental variation [ 103 ] have been reported on the genetic modification of starch. According to our knowledge, there are just a few recently published pieces of literature on the experimental genetic modification of starch.…”
Section: Modification Of Starchmentioning
confidence: 99%
“…However, the study of PIF genes in sweet potato under stress has not been reported. Due to the complicated and highly heterozygous genetic background of sweet potato, the improvement of its agronomic traits is limited [ 51 ]. With the continuous advancement of sequencing technology, the genome assembly of hexaploid sweet potato Taizhong 6 [ 52 ], and two diploid species, Ipomoea triloba NCNSP0323 (2n = 2x = 30) and Ipomoea trifida NCNSP0306 (2n = 2x = 30) have recently been completed [ 53 ], making it possible to systematically investigate important gene families in sweet potato.…”
Section: Introductionmentioning
confidence: 99%